Antioxidant and antibacterial activities of Nephelium lappaceum L. extracts - Nont Thitilertdecha (2018)
Ether, methanolic and aqueous extracts of lyophilized rambutan (Nephelium lappaceum L.) peels and seeds were evaluated for phenolic contents, antioxidant and antibacterial activities. High amounts of phenolic compounds were found in the peel extracts and the highest content was in the methanolic fraction (542.2 mg/g dry extract). Several potential antioxidant activities, including reducing power, β-carotene bleaching, linoleic peroxidation and free radical scavenging activity, were evaluated. The peel extracts exhibited higher antioxidant activity than the seed extracts in all methods determined (P < 0.05). The methanolic fraction was found to be the most active antioxidant as shown by their 50% DPPHradical dot inhibition concentration, 4.94 μg/mL. The results indicated this fraction exhibited greater DPPHradical dot radical scavenging activity than BHT and ascorbic acid (0.32 g dry extract/g BHT or ascorbic acid). Antibacterial activity against eight bacterial strains was assessed by disc diffusion and broth macrodilution methods. All peel extracts exhibited antibacterial activity against five pathogenic bacteria. The most sensitive strain, Staphylococcus epidermidis, was inhibited by the methanolic extract (MIC 2.0 mg/mL). © 2008 Swiss Society of Food Science and Technology.